Uji Analgetik Infus Daun Jambu Biji Berdaging Merah pada Mencit Jantan dengan Metode Rangsangan Kimia - Hery Prambudi (Poltekkes Kemenkes Kendari, 2020)
The flavonoids content on guava leaves has a role to improve blood circulation throughout the body and prevent the occurrence of blood vessel blockage, anti-inflammatory and analgesic. This study aims to determine whether the infusion of red fleshy guava leaves (Psidium guajava Linn.) has an analgesic effect on male mice (Mus musculus) and at what concentration the infusion of red fleshy guava leaves (Psidium guajava Linn.) has an analgesic effect on male mice (Mus musculus). The experiments were carried out using chemical stimulation methods. Analgesics or painkillers are substances that reduce or eliminate pain without losing consciousness (the difference with general anesthesia). This research is a pure experimental study using 25 mice divided into 5 treatment groups, each group consisting of 5 mice, then induced with 1% v / v acetic acid dose 50 mg / kgBB intraperitonially (ip) as pain induction, left for 15 minutes. then the treatment was carried out in each concentration group of 10% w / v, 15% w / v, and 20% w / v. Oral administration of 1% paracetamol suspension solution at a dose of 65 mg / kgBW was used as a positive control, and aquadest was used as a negative control. observations were made by counting the amount of writhing seen in 5 minutes for 60 minutes, then determined the percentage of analgesic power. The results showed that the infusion of red fleshy guava leaves (Psidium guajava Linn.) had an analgesic effect of the percentage of analgesic power of 87.88% which was close to the percentage of paracetamol analgesic power of 100%.